MIOCENE QUANTITATIVE CALCAREOUS NANNOFOSSIL BIOSTRATIGRAPHY FROM SOUTHERN APENNINES FOREDEEP DEPOSITS AND MEDITERRANEAN DSDP SITE 372 (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
A quantitative biostratigraphic study based on calcareous nannofossil assemblages was carried out in nine Miocene calcareous and siliciclastic foredeep sections, cropping out in the outer part of the Southern Apennines and generally ascribed to the external Irpinian units. Several biozonal events were recognised by means of quantitative analyses, according to the biostratigraphic schemes of Fornaciari & Rio (1996) and Fornaciari et al. (1996) for the lower and middle Miocene and of Theodoridis (1984) for the upper Miocene. In the lower and middle Miocene interval some biohorizons such as the first common occurrence of Helicosphaera walbersdorfensis and last common occurrence of Calcidiscus premacintyrei are not always detectable in the studied sections and the first common occurrence of Calcidiscus macintyrei appears to be a better biohorizon in the MNN6b/7 than the last common occurrence of C. premacintyrei. New data on abundance patterns of selected calcareous nannofossils have been collected, thus improving the biostratigraphic resolution of the zonal schemes: a paracme interval of small Reticulofenestra pseudoumbilicus was noted within Zone MNN4b and MNN5a; the beginning and the end of the paracme are useful events in the studied sections for stratigraphic correlations. Moreover the occurrence of R. pseudoumbilicus has been recorded from Zone MNN2b on upwards, fairly below the FCO of the species that defines the base of Zone MNN6b. The distributions observed in the on-land sections are consistent with those recognised in DSDP Site 372 located in the western Mediterranean Sea, confirming their potential biostratigraphic utility within the Mediterranean region.